Effects of Nitrogen and Plant Density on Competition between Two Maize Hybrids Released in Different Eras. (1st November 2017) - Zhai, Lichao; Xie, Ruizhi; Li, Shaokun; Zhang, Zhengbin
Abstract : Core Ideas: Nitrogen application rate and plant density affect competition between maize hybrids. Competitive outcomes are invariant under different N levels and plant densities. Nitrogen deficiency increased the competitive advantage of the superior competitor. Higher plant density reduced the competitive advantage of the superior competitor. Competition is a common phenomenon in plant communities, but it remains unclear whether it is influenced by soil productivity. To investigate whether N fertilization and plant density affect competition between maize ( Zea mays L.) hybrids, field experiments were conducted during the 2013 and 2014 growing seasons using a de Wit replacement series design. Two maize hybrids, YD13 and ZD909, which were released in different eras were tested. In each replacement series, dry matter accumulation (DMA), grain yield, and harvest index per plant of the component hybrids decreased as the proportion of YD13 increased under contrasting N and plant density combination. Despite different N and plant density combinations, competitive outcomes was invariant (i.e., YD13 was always the superior competitor), the yield performance of ZD909 was always higher than YD13. When the plant density was held constant, N deficiency increased both inter‐cultivar competition and the degree of competitive asymmetry between YD13 and ZD909. When the N application rate was held constant, competition intensity intensified with increasing plant density; however, the degree of competitive asymmetry was reduced, mainly because the competitive advantage of the superior competitor (YD13) diminished at higher population densities. Our results suggest that N deficiency increases the competitive advantage of a superior competitor over a weaker competitor, but this advantage decreases in response to increased plant density. This probably implies that maize hybrids with weak competitiveness should be selected in breeding programs, especially under the condition of higher soil productivity and plant density, which is designated for dense‐planting and high‐yielding production.